Training and Technical Guidance on Scientific Journal Management at The Institute for Research and Community Service Institut Sains dan Teknologi Annuqayah - Ary Iswahyudi; Ika Oktaviana Dewi; Mohammad Taufiq Shidqi; Iswahyudi Iswahyudi; Imam Wahyudi (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
Scientific journals are a means for historians to publish the results of their research and service so that their knowledge can continue to be developed and its benefits can be felt by the wider community. Scientific journals are also said to be a form of implementation for the academic community, which is presented in the form of articles or scientific papers that are closely related to the tridharma of higher education. The Institut Sains dan Teknologi Annuqayah (IST) Guluk-Guluk Sumenep has 7 journals, consisting of 1 service journal and the rest being research journals that correspond to the study programs at IST Annuqayah. Of the seven journals, only one has been running and successfully published; the rest have not yet been processed further. This community service activity aims to provide information and implement the journal management process through OJS. This PKM method is carried out by analyzing the situation and improving it, which is packaged in three stages, namely: socialization, mentoring, and evaluation. PKMini partners with 20 people to manage the IST Annuqayah journal. The results of this service show that the training participants' ability improvement index shows an average value of 88%, which means this training has succeeded in exceeding the target success rate of 70%. Then the usefulness index for this PKM activity shows a value of 18, which means this activity is very useful.